Fabrication and Characterisation of Silymarin–Quercetin Loaded Polymeric Nanoparticles Using TPGS for Hepatic Drug Delivery - Senthila Sivakami (Journal of Global Pharma Technology, 2021)
Objective: The aim of the present investigation was to enhance the hepatoprotective activity of silymarin and Quercetin by incorporating it in TPGS-PLGA nanoparticles (NPs) for passive targeted delivery, thereby prolonging its retention time. Method: Poly lactide-co-glycolide (PLGA) nanoparticles were prepared by modified spontaneous emulsification solvent diffusion (SESD) method. TPGS as an emulsifier and further as a matrix material blended with PLGA was used to enhance the encapsulation efficiency and improve the drug release profile of nanoparticles. Silymarin and Quercetin were used as model drugs which are having poor water solubility. Result: The surface morphology and size of the nanoparticles were studied by scanning electron microscopy (SEM). Drug encapsulation efficiency and in vitro drug release pattern of nanoparticles were determined using High Performance Liquid Chromatography (HPLC).The nanoparticles prepared in this study were spherical, with size range of 150–250 nm. It was shown that TPGS was a good emulsifier for producing nanoparticles of hydrophobic drugs like Silymarin and Quercetin and improving the encapsulation efficiency, drug loading and drug release profile of nanoparticles. Conclusion: This research suggests that the combined therapy system of Silymarin and Quercetin could be a better approach for liver targeted drug delivery.